The Impact of Digital Literacy and Risk Internet Behavior on Science Learning Achievement: A Case Study of Students at Junior High School 1 Kendari - Hajar, Sitti; Haetami, Aceng; Muzini, Muzini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Today’s main problem is the lack of literacy in the learning process. The use of literacy is defined as a pattern to foster and develop the process of reasoning and thinking. Currently, many children do not have literacy skills, one of which is digital literacy. Digital literacy among students and schools is often misused or misinterpreted, especially in the use of the digital internet. This study aims to describe digital literacy, risk internet behavior, and science learning achievement, as well as the simultaneous and partial influence of digital literacy and risk internet behavior on science learning achievement. This research is classified as quantitative research using the survey method. The population in this study were all students of Junior High School 1 Kendari in the 2020/202 academic year. The sampling technique in this study is proportionate stratified random sampling, i.e., population members are taken at random and proportionally stratified, consisting of classes VII, VIII, and IX. The number of samples obtained was 284 samples. The results showed that the average digital literacy of students was included in the reasonably high category, and the average risk internet behavior of students was included in the good category, meaning that they could control the bad risks arising from using the internet. The average science learning achievement of students was included in the high category. Multiple linear regression test results show that digital literacy and risk internet behavior simultaneously significantly affect science learning achievement, with a contribution of 9.4%. And the results of a simple linear regression test show that digital literacy does not substantially affect science learning achievement. This is because the contribution of digital literacy is very small, namely 0.04%, so statistically, digital literacy has no significant or no effect on science learning achievement. Meanwhile, risk internet behavior significantly influences science learning achievement, contributing 9.15%. Based on the analysis results, the internet’s use had an impact on student achievement in school. It is because many students use the internet as a learning resource.